Jasmonate-responsive MYB factors spatially repress rutin biosynthesis in Fagopyrum tataricum. (31st January 2018) - Zhang, Kaixuan; Logacheva, Maria D; Meng, Yu; Hu, Jianping; Wan, Dongpu; Li, Long; Janovská, Dagmar; Wang, Zhiyong; Georgiev, Milen I; Yu, Zhuo; Yang, Fuyu; Yan, Mingli; et al.
Abstract : Jasmonate-responsive repressors of FtMYBs can be degraded by the 26S proteasome in a COI1-dependent manner in Fagopyrum tataricum and act together with FtSAD2 or FtJAZ1 in the phenylpropanoid pathway. Abstract: Jasmonates are plant hormones that induce the accumulation of many secondary metabolites, such as rutin in buckwheat, via regulation of jasmonate-responsive transcription factors. Here, we report on the identification of a clade of jasmonate-responsive subgroup 4 MYB transcription factors, FtMYB13, FtMYB14, FtMYB15, and FtMYB16, which directly repress rutin biosynthesis in Fagopyrum tataricum . Immunoblot analysis showed that FtMYB13, FtMYB14, and FtMYB15 could be degraded via the 26S proteasome in the COI1-dependent jasmonate signaling pathway, and that this degradation is due to the SID motif in their C-terminus. Yeast two-hybrid and bimolecular fluorescence complementation assays revealed that FtMYB13, FtMYB14, and FtMYB15 interact with the importin protein Sensitive to ABA and Drought 2 (FtSAD2) in stem and inflorescence. Furthermore, the key repressor of jasmonate signaling FtJAZ1 specifically interacts with FtMYB13. Point mutation analysis showed that the conserved Asp residue of the SID domain contributes to mediating protein–protein interaction. Protoplast transient activation assays demonstrated that FtMYB13, FtMYB14, and FtMYB15 directly repress phenylalanine ammonia lyase ( FtPAL ) gene expression, and FtSAD2 and FtJAZ1 significantly promote the repressing activity of FtMYBs. These findings may ultimately be promising for further engineering of plant secondary metabolism.